Minimally Invasive Resection of a Pediatric Lumbar Osteoblastoma: Case Report. Issue 3 (7th June 2020) - Brunette-Clément, Tristan; Lavergne, Pascal; Shedid, Daniel; Weil, Alexander G
Abstract: BACKGROUND: Osteoblastomas are locally aggressive bone tumors typically affecting the posterior elements of the vertebral column. The treatment of choice is total surgical resection, traditionally through an open laminectomy, often with facetectomy and fusion when the lesion is in the foramen. OBJECTIVE: To seek an alternative to open surgery, allowing quick and full functional recovery, to meet the youth and athlete population's specific surgical goals. In this population especially, open surgery can be associated with significant impairment and morbidity. METHODS:  We report a pediatric case of posterior L5 osteoblastoma completely removed using a facet-sparing and fusion-avoiding contralateral foraminal minimally invasive approach using a tubular retractor system. A 12-yr-old male competitive tennis player presented with progressive right L5 lumbosciatica. Computed tomography scan and magnetic resonance imaging revealed a lesion of the right L5 pedicle, facet, and vertebral body with significant foraminal soft-tissue extension. Being unfit for percutaneous radiofrequency ablation, the patient underwent a minimally invasive biopsy and resection using an 18-mm-wide METRx nonexpandable tubular retractor (Medtronic) through a contralateral approach, sparing the facet and avoiding fusion surgery. RESULTS: Postoperative imaging showed residual tumor. The patient was reoperated in a similar fashion with complete tumor removal. His symptoms resolved completely postoperatively. He resumed tennis within 4 mo and remains symptom- and tumor-free at 12-mo follow-up. CONCLUSION: Minimally invasive contralateral facet-sparing resection of a pediatric lumbar osteoblastoma is an alternative to standard technique and is associated with significant advantages for young athletes, such as quick and full functional recovery, along with avoidance of fusion when the facet joint is involved.